Comparative Analysis of Vertebrate Dystrophin Loci Indicate Intron Gigantism as a Common Feature - Pozzoli, Uberto; Elgar, Greg; Cagliani, Rachele; Riva, Laura; Comi, Giacomo P.; Bresolin, Nereo; Bardoni, Alessandra; Sironi, Manuela (Genome Research, 2003)
The human DMD gene is the largest known to date, spanning > 2000 kb on the X chromosome. The gene size is mainly accounted for by huge intronic regions. We sequenced 190 kb of Fugu rubripes(pufferfish) genomic DNA corresponding to the complete dystrophin gene (FrDMD) and provide the first report of gene structure and sequence comparison among dystrophin genomic sequences from different vertebrate organisms. Almost all intron positions and phases are conserved between FrDMD and its mammalian counterparts, and the predicted protein product of the Fugu gene displays 55% identity and 71% similarity to human dystrophin. In analogy to the human gene, FrDMD presents several-fold longer than average intronic regions. Analysis of intron sequences of the human and murine genes revealed that they are extremely conserved in size and that a similar fraction of total intron length is represented by repetitive elements; moreover, our data indicate that intron expansion through repeat accumulation in the two orthologs is the result of independent insertional events. The hypothesis that intron length might be functionally relevant to the DMD gene regulation is proposed and substantiated by the finding that dystrophin intron gigantism is common to the three vertebrate genes.[Supplemental material is available online at www.genome.org.]
10.1101/gr.776503